University students involvement in cyber-bullying : a case study among UiTM students in Kota Bharu, Kelantan / Nurul Ainna Abas, Balqis Farhana Shahrom and Faizatul Nabila Khairol Amir Rashid - Abas, Nurul Ainna; Shahrom, Balqis Farhana; Khairol Amir Rashid, Faizatul Nabila (2018)
This research paper intended to examine the most significant factor contributing to students’ involvement in cyber-bullying and indirectly raise students’ awareness regarding the issue of cyber-bullying. Besides that, this study determine to study about the relationship of technological, psychological and sociological factors with UiTM Kota Bharu’s students’ involvement in cyberbullying. 116 students of UiTM Kota Bharu were selected to participate in this study through simple random sampling technique. A google form link was sent to each respondent through a messenger application called “Whatsapp” application, and also through e-mail. The information obtained was then analyzed using Multiple Linear Regression analysis. The results in this study found that only psychological factor had a significant contribution towards students’ involvement in cyber-bullying, whereas the other two factors did not have any significant effect. It was also found that the mean of cyber-bullying involvement for male students was not equal to the mean of cyber-bullying involvement for female students. Male students were found to have a greater mean of cyber-bullying involvement compared to female students